L-Methylfolate in Antidepressant Non-responders: The Impact of Body Weight and Inflammation - Macaluso, Matthew (Frontiers in Psychiatry, 2022)
This summary provides context for the role of L-methylfolate (LMF) in treating antidepressant non-responders. Bidirectional relationships have been observed between obesity and/or inflammation and depression. Studies have shown an increased prevalence of depression among patients with elevated body mass index and/or chronic inflammation and an increased risk of becoming obese and experiencing chronic inflammation in those with depression. These relationships can negatively affect the pathophysiology of depression. Elevated cytokine levels have been found to be among the factors that correlate with poor antidepressant treatment responsiveness. Low baseline neurotransmitter levels (e.g., serotonin) can also be associated with reduced effectiveness of commonly used antidepressants [e.g., selective serotonin reuptake inhibitors (SSRIs)]. LMF is an approved nutritional adjunctive antidepressant therapy that increases central neurotransmitter levels and thereby improves the effectiveness of antidepressant therapy. LMF can increase clinical response when used adjunctively in patients with major depressive disorder (MDD) and who are SSRI-resistant. In 2 randomized controlled trials, the pooled results showed increased response rates (32.3 vs. 14.6%; P = 0.04) as measured by a ≥50% reduction or final score ≤ 7 on the Hamilton Depression Rating Scale (HAM-D) and greater mean HAM-D reductions (−5.6 vs. −3.0; P = 0.05) when LMF was added to an SSRI compared with an SSRI plus placebo. Additionally, LMF has demonstrated effectiveness in real-world studies, with 67.9% of patients responding to therapy, using the 9-item Patient Health Questionnaire (P < 0.001). Post-hoc analyses found that patients with inflammation and/or obesity responded better to adjunctive LMF therapy compared with the overall sample (mean HAM-D reduction: −2.74 vs. +0.99).